Implementasi Dakwah Rasulullah dalam Era Milenium - Arif, Mohammad (Asketik: Jurnal Agama dan Perubahan Sosial, 2020)
Humans as subjects and objects of law cannot live and carry out lawsuits. But instead, humans are bound by a rule that applies in the midst of their lives as citizens in their environment. For this reason, awareness is needed in understanding and obey the rules that apply. But social and cultural changes that occur continuously sometimes bring hope as well as concern. Hope, because change will bring better conditions, and fears will come if the future is worse than the present. The development of science and technology that should have raised hopes and reduced concerns are now also marked by the confrontation of scientists and scholars, namely the separation between the world and the hereafter, making it difficult to control human attitudes as the excesses of the emptiness of the soul. Helping the general public requires the ability to wage jihad in the field of da'wah. The insistent pressure in the Prophet's preaching in Mecca then inspired the Prophet to emigrate and temporarily exit from Mecca to Medina. The original name of the city was Yastrib. This Prophet's strategy turned out to be very telling and presented a golden journey in the history of da'wah and the formation of society. With all the intelligence and attitudes of the Prophet Muhammad, when in Medina not only can spread in the sense of tabli but more than that the Prophet Together the community can build a model of a modern social system even too modern in its time. Helping the general public requires the ability to wage jihad in the field of da'wah. The insistent pressure in the Prophet's preaching in Mecca then inspired the Prophet to emigrate and temporarily exit from Mecca to Medina. The original name of the city was Yastrib. This Prophet's strategy turned out to be very telling and presented a golden journey in the history of da'wah and the formation of society. With all the intelligence and attitudes of the Prophet Muhammad, when in Medina not only can spread in the sense of tabli but more than that the Prophet Together the community can build a model of a modern social system even too modern in its time